2016
DOI: 10.1007/s12325-016-0293-x
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Considerations for the Treatment of Hospital-Acquired Pneumonia

Abstract: Hospital-acquired pneumonia (HAP) and health-care-associated pneumonia (HCAP) are leading causes of death, morbidity, and resource utilization in hospitalized patients, and are associated with a broad range of Gram-positive and Gram-negative pathogens. Here, we discuss the different definitions of HAP and HCAP, review current guidelines regarding the treatment of these conditions, highlight the shortcomings of current therapeutic options, and discuss new antibiotic treatments. To optimize therapeutic outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…Our results are consistent with previous studies. 11 , 22 , 27 , 32 For instance, Jahansefat et al 36 claimed that the attitude of healthcare workers towards VAP prevention is not very positive, and Özveren and Özden 31 that 68.1% of the participants said that cleaning the oral cavity is a difficult and unpleasant task. However, our result is higher than Saddki et al 37 which revealed that 40.8% of the participants stated it was difficult and 16.2% unpleasant, using appropriate oral care methods and having positive oral care attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with previous studies. 11 , 22 , 27 , 32 For instance, Jahansefat et al 36 claimed that the attitude of healthcare workers towards VAP prevention is not very positive, and Özveren and Özden 31 that 68.1% of the participants said that cleaning the oral cavity is a difficult and unpleasant task. However, our result is higher than Saddki et al 37 which revealed that 40.8% of the participants stated it was difficult and 16.2% unpleasant, using appropriate oral care methods and having positive oral care attitudes.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 19 One of the most effective oral care practices is brushing the patient’s mouth using chlorhexadine plus use of a broad-spectrum antibiotic agent. 1 , 9 , 20 - 22 The recommended frequency of performing oral care also varies: every 2 hours, 4 hours, 8 hours or 12 hours. 9 , 13 , 19 , 23 - 25 The literature did not confirm which was better for reducing the risk of VAP.…”
mentioning
confidence: 99%
“…HAP incidence ranges from 5 to more than 20 cases per 1000 hospital admissions, with the highest rates in immunocompromised, post-surgery and elderly patients [3,[40][41][42][43]. However, in contrast to VAP patients in whom it is relatively easy to collect distal respiratory secretions through the endotracheal tube as soon as the infection is suspected and before the introduction of any new antibiotics, obtaining reliable specimens from the lower respiratory tract for microbiological cultures in patients developing HAP is difficult and thus most of them are receiving new antibiotics before specimens can be obtained.…”
Section: Microbial Etiologies Of Hapmentioning
confidence: 99%
“…European studies tend to report community-like etiology, while studies from Asia and the US show increased MDRO rates in HCAP patients [ 25 28 ]. To date, the clinical relevance of HCAP remains unclear [ 23 , 24 ]. In fact, both Infectious Diseases Society of America (IDSA) and European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guidelines do not address HCAP, which leaves a gap in the recommendations regarding treatment for patients from long-term care facilities (LTCFs).…”
Section: Microbiological Etiologymentioning
confidence: 99%